(untitled) (International Journal of Irrigation and Water Management, 2020)
Nowadays, due to rain variability with a groundwater decrease, water resource became scarce in the main irrigated plains in Burkina Faso. Thus, rice is gradually being replaced by other crops which have low water need principally in Bama irrigated plain during off-season. This study aimed to analyze the efficiency of current irrigation practices during dry season rice farming in Bama plain. Hence, fifteen peasant crop-production practices in their plot of 0.5 ha during 2018 off-season from February to June have been followed. The irrigation water supplied was much lower than rice water requirements, average 61% of ETR. In addition, 28.8% of the yield has been determined by quantity of water applied with average water productivity of 0.8kg.m3.